Serum 25-hydroxy vitamin D level is associated with elastography-detected liver fibrosis in patients with type 2 diabetes mellitus in China - Huang, Nan; Su, Xianghui; Yu, Ting; Wu, Xiaodong; Lu, Bing; Sun, Weixia; Yao, Liqin; Wang, Maoyun; Wang, Yao; Wu, Wenxuan; Liu, Yingzhao; Yang, Ting; et al. (Frontiers in Endocrinology, 2024)
Objective: In this cross-sectional study including patients with type 2 diabetes mellitus (T2DM) we aimed to explore the relationship between serum 25-hydroxy vitamin (25(OH)D) level and liver steatosis and fibrosis in Chinese population.Patients visiting 16 clinical centers with T2DM were recruited. The status of liver steatosis and fibrosis were then assessed using elastography examination.Associating factors of steatosis and fibrosis were explored using regression analysis.Correlations between serum 25(OH)D levels with other patient characteristics were analyzed using linear regression.Results: Totally 1513 T2DM patients were included in the study period. The prevalence of steatosis and fibrosis were 69.7%, and 34.6%, separately. A lower level of 25(OH)D was detected in patients with liver steatosis compared to those without, although it was not an independent predictor of this condition. However, 25(OH)D level was independently associated with liver fibrosis even when adjusted to age, sex, BMI, HbA1c, insulin, and HOMA-IR (OR = 0.964 [0.935-0.993], P = 0.015). When patients were separated into subgroups of different gender, correlations between 25(OH)D and fibrosis were identified in male group (OR = 0.969 [0.940-0.998], P = 0.038).In conclusion, this multi-center, cross-sectional study in T2DM patients showed that serum 25-hydroxy vitamin D level is strongly associated with liver fibrosis, and this relationship was more pronounced in male patients.